Contrast-enhanced ultrasound findings of hepatic pseudolipoma: a case report - Jiang, Luyao; Yuan, Zhiqiang; Luo, Yan (Frontiers in Oncology, 2025)
BackgroundHepatic pseudolipoma is a relatively rare benign tumor of the liver in primary hepatic lesions and is characterized by focal fat around the liver capsule. It typically affects older adult men. In this case report, we discuss the case of a 71-year-old male who presented to our hospital with rectal adenocarcinoma. A pseudolipoma was incidentally detected on a preoperative computed tomography scan of the abdomen. We performed contrast-enhanced ultrasound to clarify the nature of this tumor. To the best of our knowledge, there have not been any documented reports on contrast-enhanced ultrasound findings of hepatic pseudolipoma.FindingsHepatic pseudolipoma appears on contrast-enhanced ultrasound as slightly hyperechoic nodule with poorly defined borders and regular morphology. DiagnosisOn the basis of the patient’s clinical symptoms, test results, and imaging manifestations, the lesion was considered a pseudolipoma, not a liver metastasis from rectal cancer. Pseudolipoma usually does not need treatment.ConclusionThe current report will help enhance the current knowledge regarding identifying hepatic pseudolipoma by contrast-enhanced ultrasound imaging and review the related literature.